Decline in head growth and cognitive impairment in survivors of acute lymphoblastic leukaemia. Issue 5 (May 1990) - Appleton, R E; Farrell, K; Zaide, J; Rogers, P
Abstract : Twenty five children in remission, who were asymptomatic and who had last been treated at least two years before for acute lymphoblastic leukaemia, were examined neurologically and neuropsychologically. Their treatment included early cranial irradiation (24 Gy or 18 Gy), intrathecal methotrexate, and systemic chemotherapy. One half of the children demonstrated a decline in head circumference centile, which occurred in all patients treated with 24 Gy and in those patients treated with 18 Gy under the age of 3 years. In those children whose head growth was reduced, performance was significantly impaired in neuropsychological tests designed to assess concentration and short term memory. These children also developed clinically important learning difficulties in the classroom. Minor neurological dysfunction was present in almost half of the entire group. These data suggest that the treatment employed to prevent central nervous system leukaemia (primarily cranial irradiation) has a deleterious effect on head and brain growth and intellectual function.